Avoiding, diagnosing and treating well leg compartment syndrome after pelvic surgery. Issue 9 (15th July 2019) - Gill, M.; Fligelstone, L.; Keating, J.; Jayne, D. G.; Renton, S.; Shearman, C. P.; Carlson, G. L.; ,
Abstract : Background: Patients undergoing prolonged pelvic surgery may develop compartment syndrome of one or both lower limbs in the absence of direct trauma or pre‐existing vascular disease (well leg compartment syndrome). This condition may have devastating consequences for postoperative recovery, including loss of life or limb, and irreversible disability. Methods: These guidelines represent the collaboration of a multidisciplinary group of colorectal, vascular and orthopaedic surgeons, acting on behalf of their specialty associations in the UK and Ireland. A systematic analysis of the available peer‐reviewed literature was undertaken to provide an evidence base from which these guidelines were developed. Results: These guidelines encompass the risk factors (both patient‐ and procedure‐related), diagnosis and management of the condition. Key recommendations for the adoption of perioperative strategies to facilitate prevention and effective treatment of well leg compartment syndrome are presented. Conclusion: All surgeons who carry out abdominopelvic surgical procedures should be aware of well leg compartment syndrome, and instigate policies within their own institution to reduce the risk of this potentially life‐changing complication. Abstract : This article reviews the published literature relating to the aetiology, pathophysiology, clinical features, diagnosis and management of lower limb compartment syndrome after pelvic surgery. Guidelines on prevention, diagnosis and management, endorsed by the relevant surgical specialty associations, are presented. Rare, but preventable